Universal noir #1 - Gielgud, Irwin (Universal Studios, 2022)
"Newspaperman helps girl find her sister's illegitimate baby, gets mixed up in baby-adoption racket." [imdb.com]
Original: USA 1949
Limited edition Blu-ray box set special features: 2010 High Definition remaster ; original mono audio ; audio commentary with writers and film experts Barry Forshaw and Kim Newman (2022) ; Easy to get (1947, 22 mins): short film made as part of the US Armed Forces’ ‘Easy to get’ campaign on venereal diseases, directed by Joseph M Newman ; image gallery: promotional and publicity material ; new and improved English subtitles for the deaf and hard of hearing ; UK premiere on Blu-ray
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc